Pengaruh Green Accounting, Kinerja Lingkungan, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia - Daffa Rinaldi Pratama; Ratiyah Ratiyah; Eni Reptiningsih; Hartanti Hartanti; Eka Dyah Setyaningsih (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of Green Accounting, environmental performance, and company size on company value in mining sector companies listed on the Indonesia Stock Exchange (BEI). This research is quantitative research using secondary data. The samples in this research obtained using certain criteria sampling techniques were PROPER participating companies registered on the IDX throughout 2019-2023. The statistical method used in this research is multiple regression analysis. The results of this research show that simultaneously, the independent variables in the form of Green Accounting, environmental performance and company size influence company value. Partially, the Green Accounting variable has a positive and significant effect on company value, the environmental performance variable also has a positive and significant effect on company value, and the company size variable has a positive and significant effect on company value.